1996
DOI: 10.1557/proc-457-231
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Microstructure of a Nanocrystalline Ferromagnet - Micromagnetic Model and Small-Angle Neutron Scattering

Abstract: We report on a combined theoretical and experimental study of the magnetic microstructure of a single component, single phase, Pore-free nanocrystalline ferromagnetic material. From the equations of micro-magnetics we conclude that the magnetic microstructure is the convolution product of an anisotropy field microstructure and of a response function with a correlation length lH that depends on the applied field Ha. We derive equations for small angle neutron scattering by such structures, and present experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
3
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 13 publications
2
3
0
Order By: Relevance
“…Studies of dislocation arrays in cold-worked ferromagnetic single crystals have demonstrated that a combination of SANS experiments with micro-magnetics theory can provide information on the nuclear microstructure [ 18 ]. Preliminary results of the present study [ 19 ] indicated that SANS experiments on single-phase bulk nanocrystalline materials with low porosity, hence low nuclear scattering cross-section, are in good agreement with predictions from micromagnetics over a wide range of applied magnetic fields and scattering vectors.…”
Section: Introductionsupporting
confidence: 82%
“…Studies of dislocation arrays in cold-worked ferromagnetic single crystals have demonstrated that a combination of SANS experiments with micro-magnetics theory can provide information on the nuclear microstructure [ 18 ]. Preliminary results of the present study [ 19 ] indicated that SANS experiments on single-phase bulk nanocrystalline materials with low porosity, hence low nuclear scattering cross-section, are in good agreement with predictions from micromagnetics over a wide range of applied magnetic fields and scattering vectors.…”
Section: Introductionsupporting
confidence: 82%
“…Bakonyi et al [12] observed the same trend for nanocrystalline Ni, also prepared by electrodeposition. Weissmüller, et al [79] confirmed the earlier measurements by Aus et al, [73] reporting only small changes in M s for electrodeposited nanocrystalline Ni with 18 nm grain size. Kisker et al [80] presented further results for gas-condensed Ni which, in contrast to their earlier work, [70] now showed the saturation magnetization to be independent of grain size as long as the gas-condensed material was not exposed to air.…”
Section: Saturation Magnetizationsupporting
confidence: 73%
“…At present, the only known technique with a potential to resolve the magnetic microstructure in the bulk and on the length scale of nanometers is magnetic smallangle neutron scattering (SANS). SANS data have provided insight into the magnetic microstructure of soft magnetic nanocrystalline samples [2][3][4][5], yielding quantitative results for the magnetic microstructure, the exchange-stiffness constant, and the magnitude and microstructure of the magnetic anisotropy [5,6]. We have investigated nanocrystalline Tb as a model nanocrystalline hard magnet; the present paper complements a first report of the scattering data [7] with results of the magnetic characterization.…”
mentioning
confidence: 78%